Optimization of Digital Technology Utilization for Improving the Skills of Karang Taruna in Nagari Sungai Beringin, 50 Kota Regency - yeka Hendriyani; Syafrijon Syafrijon; Yudhi Diputra (Universitas Negeri Padang, 2026)
This community service activity aimed to optimize the use of digital technology to improve the skills of Karang Taruna members in Nagari Sungai Beringin, 50 Kota Regency. The activity was motivated by several problems, including limited access to digital technology, low digital skills among youth, and the absence of structured skill development programs relevant to current needs. The solution offered was training on the use of Canva for social media content design and logo creation to support youth creativity and entrepreneurship. The program involved 22 participants and was conducted on September 6–7, 2024. The implementation methods included preparation, pretest, training sessions, guided practice, independent assignments, posttest, and participant response questionnaires. The results showed that the training was carried out well and received positive responses from participants. The activity increased participants’ interest, confidence, and practical skills in designing digital content. Participants were able to produce valid and usable social media designs and logo products for Karang Taruna. This activity demonstrates that digital technology-based training can be an effective strategy for strengthening youth capacity, encouraging productive creativity, and supporting community empowerment at the village level.